2019
DOI: 10.7812/tpp/18.244
|View full text |Cite
|
Sign up to set email alerts
|

ECG Diagnosis: Dextrocardia

Abstract: This observational study involved sequential implementation of a multidisciplinary team, protocols, and a craniotomy pathway. Retrospective review of admissions (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017) revealed reduced craniotomy complication rates, case volume increased 73%, and hospital length of stay improved by 63%, as well as increased professional collegiality and satisfaction. A searchable craniotomy discharge summary is an important tool for continuous monitoring of quality and effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“… 11 Leads placed in a mirror location may provide reliable ECG data for patients with dextrocardia. 14 In the present case, the ideal position of the catheter tip was discovered by reversing lead II of the intracavitary ECG. Post-procedure chest radiography revealed that the tip of the catheter was positioned in the inferior vena cava and located 3.01 cm below the tracheal carina.…”
Section: Discussionmentioning
confidence: 55%
“… 11 Leads placed in a mirror location may provide reliable ECG data for patients with dextrocardia. 14 In the present case, the ideal position of the catheter tip was discovered by reversing lead II of the intracavitary ECG. Post-procedure chest radiography revealed that the tip of the catheter was positioned in the inferior vena cava and located 3.01 cm below the tracheal carina.…”
Section: Discussionmentioning
confidence: 55%
“…In patients with a true dextrocardia in situs inversus, EKG can reveal right axis deviation, a negative QRS complex, inverted P and T waves in lead I, biphasic T waves, and progressively decreasing R-wave amplitude from leads V1 to V6 [4]. These findings were notably absent in this patient.…”
Section: Dextroposition or Dextrocardia?mentioning
confidence: 57%
“…ECG programmers have struggled for years to produce algorithms to detect such diagnoses. 2 It is important that clinicians develop proficiency in being able to differentiate dextrocardia, limb lead reversal, and pseudodextrocardia.…”
Section: Discussion/rationalementioning
confidence: 99%